Hubungan Antara Stres Akademik dan Student Engagement Siswa SMA pada Masa Pandemi Covid-19 - Rita Nunung Tri Kusyanti (Ideguru: Jurnal Karya Ilmiah Guru, 2021)
This study aims to determine the relationship between academic stress and student engagement of high school students during the pandemic. The research hypothesis is that there is a negative relationship between academic stress and student engagement, meaning that the higher the academic stress, the lower the value of student engagement. The research subjects were 180 students of class X, XI and XII of SMA Negeri 1 Tempel Sleman. The data collection instruments used an academic stress scale and scale student engagement which were adapted and developed by researchers. The academic stress scale has a reliability coefficient of 0.921 and thescale student engagement has a reliability coefficient of 0.738. The data analysis technique used the Pearson product moment correlation test because the data distribution of the two variables was normal and had a linear relationship. The results of the correlation test using the product moment correlation test based on the significance value (2-tailed) amounted to 0.599> 0.05, meaning that there is no significant correlation between the academic stress variable and thevariable student engagement. The result of the value of r count (Pearson correlation) is -0.39, meaning that the value of 0.39 is greater than r table 0.148, so the two variables of academic stress and student engagement have a relationship, the strength of the relationship between academic stress and student engagement during the pandemic at SMAN 1 Paste have a low relationship. The two variables have a negative relationship because the Pearson correlation value is negative, meaning that if student engagement is low, academic stress is high or if academic stress is low, student engagement on distance learning is high.